Risk Management Strategy Implementation for Business Plan at Material Handling Rental Services Startup LogisMe - Suryanto Suryanto; Rhian Indradewa; Edi Hamdi; Ketut Sunaryanto (Dinasti Review, 2024)
PT. LogisMe Berkat Bersama (LBB) is a Limited Liability Company (PT) engaged in the business of providing Business-to-Business (B2B) warehousing and logistics solutions. LogisMe has the tagline